Multiple recycling of a PLA/PHB biopolymer blend for sustainable packaging applications: Rheology‐morphology, thermal, and mechanical performance analysis. Issue 6 (26th March 2022) - Farias, Naiara C.; Major, Ian; Devine, Declan; Brennan Fournet, Margaret; Pezzoli, Romina; Farshbaf Taghinezhad, Soheil; Hesabi, Mohammadnabi
Abstract: Blends of poly(lactic acid) (PLA)/poly(3‐hydroxybutyrate) (PHB) (70/30 wt%) were prepared, and the effects of multiple mechanical recycling up to 5 times on the rheology–morphology relationships, thermal, and mechanical properties were investigated. Rheological and morphological investigations indicated a degree of immiscibility of two combined polymers. Notably, recycling served to improve the interfacial interaction of the phases through limited transesterification reactions and increased homogeneous morphologies. While there was significant reduction in viscosity through multiple recycling, chain scission and degradation were not observed in Fourier transform infrared (FTIR) results. Additionally, higher crystallinity and lower Tg and cold crystallization temperatures were measured for the reprocessed samples, which are attributed to the formation of finer PHB droplets acting as nucleating agents promoting further crystallinity. In conclusion, the increased crystallinity counter influenced the measured viscosity decrease, and subsequently, multiple recycling was not observed to significantly affect the tensile properties. Furthermore, impact results are also indicative of the crucial role of crystallinity and blend morphology on maintaining the toughness of the recycled samples. Abstract : PLA/PHB (70/30 wt.%) blend was prepared and reprocessed for 5 times through an industrial scale twin screw extruder. Multiple recycling partially improved interfacial interaction of the two phases through limited transesterification reactions resulting in finer droplet dispersion of PHB within PLA matrix and with no distinct border observed between the two phases. Multiple recycling improved the crystallinity of the blend and thereby higher crystallinity acted to compensate for the adverse effects of recycling on the mechanical properties.